Новая гыданская (юрибейская) находка мамонта - Верещагин, Н.К. (Вестник зоологии, 1982)
September 1979 a joint expedition of biological institutes of the USSRAcademy of Sciences examined remains o ft h e mammoth female carcass occured in the frozen sands and muds of the Yuribey river right bank in the centre of the Gydansk Penin- sula. A nurished animal at the age or 10 to b vears was Kiled in late summer some 10,000 years ago. The carcass fixed on its back in horisontal position was covered b a 4 m layer of deposits. A rich mass of wool, more than 50 bones, fragments of muscles and fat, intestines containing grassy mass remained preserved.